2020
DOI: 10.1155/2020/9371967
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of Anaemia in Patients with Acute Decompensated Heart Failure

Abstract: Anaemia is a common comorbidity in patients with heart failure (HF) and is associated with more severe symptoms and increased mortality. The aim of this study was to evaluate haemodynamic profiles of HF patients with respect to the presence of reduced left ventricular ejection fraction (LVEF) and anaemia. Methods and Results. Haemodynamic status was evaluated in 97 patients with acute decompensated HF. Impedance cardiography, echocardiography, and N-terminal probrain natriuretic peptide (NT-proBNP) results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Anemia might be a risk factor for adverse events in many cardiovascular conditions, such as heart failure, 13,14 CAD after acute coronary syndrome 15 or percutaneous coronary intervention (PCI), especially when the patient requires antiplatelet medication 16 . It might also increase the risk of bleeding complication.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia might be a risk factor for adverse events in many cardiovascular conditions, such as heart failure, 13,14 CAD after acute coronary syndrome 15 or percutaneous coronary intervention (PCI), especially when the patient requires antiplatelet medication 16 . It might also increase the risk of bleeding complication.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia in HF might also exacerbate the decompensation of HF: chronic anaemia has been linked to the retention of salt and water, a reduction in renal blood flow and the glomerular filtration rate, and neurohormonal activation, which implement the congestion status commonly observed in HF patients [ 17 ]. Krzesiński et al [ 39 ] effectively demonstrated increased thoracic fluid content—as assessed by impedance cardiography—in patients with AHF, as well as higher NT-proBNP. Our data were in line with these findings: we observed higher HI values—as assessed by BIVA ( Figure 2 E,F)—in HF patients with anaemia, as well as increased values of BNP ( Figure 2 C,D).…”
Section: Discussionmentioning
confidence: 99%
“…After numerous modification, ICG is still used for research purposes [18,19]. It was employed in studies in patients with heart failure, hypertension [20,21], children with congenital heart disease [22], and individuals with sleep apnea [23,24], chronic obstructive pulmonary disease (COPD) [25,26], and pulmonary hypertension [27,28]. Despite significant limitations of ICG [29], the method has been approved by the US Food and Drug Administration.…”
Section: Practical Applications Of Icgmentioning
confidence: 99%